2013
DOI: 10.9734/ajea/2013/2947
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Potential of Centrosema pubescens Mimosa invisa and Pueraria phaseoloides Leaf Meals on Growth Performance Responses of Broiler Chickens

Abstract: Aims:The objective of this study was to access the growth responses of chickens fed different leaf meal supplements. Study Design: The experimental design used was completely randomized design for the chicks and completely randomized block design for the growing pullets and cockerels. Place and Duration of Study:The experiments were carried out at Bora Poultry Unit of Federal College of Animal Health and Production Technology, Institute of Agricultural Research and Training (IAR&T) Ibadan, Nigeria. The experim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…These plants are also used for flooring and furniture [ 16 , 17 ]. The leaves of the plants are used for chicken diet [ 18 ], as colorants in the textile industry and also play a role as additives in the food industry [ 19 , 20 ]. The trash of the poultry industry enhances the growth of the Mimosa tree [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…These plants are also used for flooring and furniture [ 16 , 17 ]. The leaves of the plants are used for chicken diet [ 18 ], as colorants in the textile industry and also play a role as additives in the food industry [ 19 , 20 ]. The trash of the poultry industry enhances the growth of the Mimosa tree [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The ash contents decreased marginally with increase in planting distance while EE content of the seeds recorded a significant increase as the planting distance was increased from 30cm x 30cm to 60cm x 60cm. The range values of GE (400.1-426.0Kcal/100g)) of Clitoria ternatea seeds were lower than 4354kcal/kg reported by Nworgu and Egbunike (2013). Except the ash constituent of the seeds that was independent of planting distances, planting distance did influence other proximate parameters and gross energy contents of the legume seeds in derived savannah zone of Nigeria.…”
Section: Proximate (%) and Gross Energy (Kcal/100g) Compositions Of Smentioning
confidence: 54%
“…Average body weight: There were no significant treatment effects observed on d 7; however, birds fed KLM had a 7.8 and 8.5% lower average body weight than birds on the control diet on d 14 and 21, respectively. Nworgu and Egbunike [24] observed that weight gain decreased when supplementing increasing levels of tropical kudzu (Pueraria phaseoloides) in broiler diets. Overall, a number of studies have shown that a majority of leaf meals depress feed consumption, thus decreasing body weight gain.…”
Section: Discussionmentioning
confidence: 99%
“…Polk and Gieger [8] demonstrated that an inclusion rate of 9% kudzu leaf meal could be supplemented in place of alfalfa meal in chick diets. Additionally, Nworgu and Egbunike [24] fed Pueraria phaseoloides leaf meal (PLM) to broilers. They concluded that PLM should not be used while rearing broilers as it decreased growth rate.…”
Section: Introductionmentioning
confidence: 99%